Synthesis , Characterization , and study of the Spectral and Electronic Properties of a New Azo Dyes Compounds - Majeed, Hasanain (University of Thi-Qar Journal of Science, 2013)
In this study two new azo dyes were prepared from 4-acetaminophenol with 4-amino-N-2-pyrimidinyl_ benzenesulfonamide & 4-amino-N-(5-methyl-3-isoxazolyl)-benzenesulfonamide were prepared. The preparedby Fox method, the azo dyes were identified by IR- spectrophotometer, UV-visible spectroscopy andelemental analysis (CHN). The absorption spectra of the azo dye was recorded with wavelength in the range(360-600) nm in universal buffer solution of different pH values. From these spectra, the ionization andprotonation constant were calculated by using the half height method. It found that the value of the ionizationconstant (pKa) closely which interpret the ionization of the hydroxyl group. Theoretical calculations for azodyes were studied by quantum chemical calculations. The optimized structures of the azo dyes were obtainedby molecular mechanics (MM+), and then further geometry optimization was carried out by the semiempirical molecular orbital theory at the level of AM1 of the theory. Study Shown, the configuration II morestable because of have high energy gap ΔE and high stability. Also the dipole moment, heats of formation,molecular orbitals energy of HOMO and LUMO were calculated.